Some reflections on Chiovenda and his legacy for Latin America: Lauditio - Pérez Ragone, Álvaro (2017)
Chiovenda was born in Premosello on February 2, 1872. He studied law at the University of Rome between 1899 and 1893, Vittorio Scialoja was a important influence pursuing that Italian procedural science was in a state of abandonment that needed attention and urged in that sense.From positive law, history, contact with overwhelming German science and aware of the lethargic Spanish and French doctrine encouraged Chiovenda to a comparative and integral formation from the dogmatic and historical.